Anatomic - morphological features of qualified water polo players depending on game role - O. V. Poproshaev; O. V. Chumakov (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : to analyze the anatomic - morphological features of qualified water polo players depending on game role. Material : the study group consisted of 41 athlete. Assessing the level of physical development was carried out in terms of water polo in body size, body weight, chest excursion, lung capacity, power brush. Results : it was found that the central strikers - powerful players with significant muscle mass. They are the following indicators: length of the arm (22%), the length of the tibia (11%), foot length (7%), shoulder width (10%) and vital capacity (11%). Central defenders - tall, sinewy athletes, which is characterized by long limbs. They highlighted the special role of the indicator arm's length (part of which is 34 %) and vital capacity (10%). Midfielders or moving forwards - players of medium height and basic anthropometric indicators inferior players other roles, but exceed them in the values of the indicator lung capacity. Conclusion : these results relate to the functions that do the athletes on the field.